Influence Of Organizational Climate, Engagement, And Commitment On Performance With Leadership As Moderation Variables - Noorfallah, Hiysman; Mutmainah, Isbandriyati; Rumna, Rumna (Jurnal Ilmiah Manajemen Kesatuan, 2024)
The purpose of the study is to determine the Organizational Climate, Engagement, and Commitment simultaneously on Performance with Leadership as a Moderation Variable (Empirical Study on ASN Directorate General of Regional Development, Ministry of Home Affairs). This study uses a type of causal associative research with a quantitative approach. The population in this case is all SUPD III employees and the total sample used is 67 respondents with a sampling technique using the Krecjie Table. Data collection was carried out by distributing questionnaires with data analysis using validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression analysis, moderation regression analysis, determination test, t test and f test. Based on the results of the T test, it is known that each independent variable of Organizational Climate, Engagement , and Commitment has an effect on Performance. In the Coefficient of Determination (R2) test, it can be seen that the Adjusted R Square value obtained is 0.580 (58%). This shows that the independent variables of Organizational Climate, Engagement, and Commitment have a strong ability to explain the bound variables (Perfromance) in this case learning. The remaining 42% was influenced by other factors that could not be explained in this study. Keywords: Organizational Climate, Engagement, Commitment, Performance, Leadership.